RAGAM ALTERNATIF STRATEGI PEMBELAJARAN PAI SELAMA MASA PANDEMI COVID-19 DI SDIT AL-MUNADI MEDAN - Masruroh Lubis; Marini Nasution; Citra Gemilasari; Fandy Fakhruddin (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2020)
This study aims to analyze: 1) The policies implemented by schools in the learning process during the Covid-19 pandemic. 2) Various alternative PAI learning strategies applied by Islamic Education teachers. 3) The impact of various alternative Islamic education strategies during the Covid-19 pandemic. 4) The obstacles to the alternative variety of PAI learning strategies experienced by teachers and students. This research was conducted at SDIT Al-Munadi Medan. The research method used is a qualitative research method, with a descriptive study model. The results of the research show that the policies set at SDIT Al-Munadi Medan during the Covid-19 emergency period continue to carry out learning. There are 2 learning alternatives that are applied, namely offline and online. Offline learning is carried out at school 2 times a week for each student by paying attention to health protocols, and online learning is carried out online based on an internet network. Variety of Alternative Islamic Education Learning Strategies The teacher sends videos of Islamic Education learning materials, and occasionally learns Islamic Education online with video calls and google meet.